The Effect of Heat Treatment on the Microstructure and Properties of H13ESR Large Mould Steel Forging Round Bar - Li Jin, Zhou Xu, Su Chao, Yan Lei (Teshugang)
In order to meet the technical requirements of H13ESR large sizes and high-quality mould steel forged round metallographic structure and impact energy， three heat treatment processes were used to trial-produce forged round bar with diameter of 600 mm H13ESR and the inspection results were compared.The experiments have shown that： online water cooling after forged and spheroidization annealing can obtain metallographic structure NADCA#229—2016 standard AS9 at the center， and the transverse impact energy of KV2 in the center is 9.8 J； The metallographic structure is AS4 at the center by forging online water cooling ，then offline solid solution（solid solution temperature 1 040 ℃-1 060 ℃， water and air cooling alternating quenching） and spheroidization annealing， and the transverse impact energy of KV2 in the center is increased to 18.3 J；The metallographic structure is AS4 at the center by air cooling after forging，then same offline solid solution and spheroidization annealing， and the transverse impact energy of KV2 in the center is increased to 17.4 J.The experiments show that：offline solid solution heat treatment process （solid solution temperature 1 040 ℃-1 060 ℃、water and air cooling alternating quenching）， and then spheroidization annealing （850 ℃-870 ℃，730 ℃-750 ℃） can obtain metallographic structure with AS4 at the center and the transverse impact energy of KV2 in the center is increased to 17.4-18.3 J， effectively improving the microstructure and properties of H13ESR steel， meet the technical requirements of high-quality H13ESR large mold steel forging round bar.